Income Diversification of Rural Households in Zoba Maekel, Eritrea - Teame, Ghirmai Tesfamariam (Archives of Business Research, 2018)
The study, conducted in Zoba Maekel, Eritrea, has examined the factors affecting the diversification of income of rural households using two concepts of diversification. The first one is based on household’s diversification away from their own farm, which is measured as the proportion of rural households’ income from non-farm activities in their total income; whereas the second one focuses on diversification as an increase in the number of rural households’ income earning activities regardless of their sectoral or functional classification, which is measured using Shannon equitability index. The study has reported that household’s income diversifications are highly related to their access to formal credit, livestock possessions, and year of schooling of household’s head or average year of schooling of members of the household. Moreover, it has supported the hypothesis that diversification is an ex-post coping strategy for low agricultural productivity, and confirmed the presence gender bias in the overall diversification of rural households.